Indexing languages in information Management, a promising future or an obsolete resource - Jose Antonio Moreiro; Jorge Morato; Sonia Sanchez-Cuadrado; Anabel Fraga (tripleC: Communication, Capitalism & Critique)
Indexing languages have traditionally been an essential tool for organizing and retrieving documental information. The inclusion of indexing languages into the digital environment leads to new frontiers, but also new opportunities. This study shows the historical evolution of the indexing languages and its application in document management field. We analyze diverse trends for their digital use from two perspectives: its integration with other digital and linguistic resources, and the adjustment of it to the Web environment. Finally, it is analyzed how these languages are used in the Web 2.0, and the incorporation of ontologies in the Semantic Web.